Over sea, under stone - Cooper, Susan, 1935- (Cooper, Susan, 1935- Dark is rising sequence., 2000)
Three children on a holiday in Cornwall find an ancient manuscript which sends them on a dangerous quest for a grail that would reveal the true story of King Arthur.